Erratum: Exon-disrupting deletions of NRXN1 in idiopathic generalized epilepsy (Epilepsia (2013) 54 (256-264) DOI:10.1111/epi.12517) - (:unkn) unknown (Blackwell Publishing Inc., 2013)
[No abstract available]